On the reversibility of structural reforms - Nauro F. Campos; Roman Horváth (Institute for the Study of Labor (IZA), 2012)
What are the factors that explain reversals in the implementation of structural reforms? Our main hypothesis is that reversals in different reforms are driven by different factors. This paper uses new reform indicators and presents novel evidence showing that (a) FDI inflows reduce the likelihood of privatization reversals, (b) worsened terms of trade increase the probability of external liberalization reversals and (c) labour strikes propel reversals in the liberalization of wages and prices.
urn:nbn:de:101:1-2012081412470
Keywords: E23; D72; H26; O17; 330; reform reversals; price liberalization; trade liberalization; privatization; political economy; Wirtschaftsreform; Deregulierung; Privatisierung; Außenhandelsliberalisierung; Public Choice